Facility Layout Redesign Using ARC and ARD Methods: Perancangan Ulang Tata Letak Fasilitas Menggunakan Metode ARC dan ARD - Nadia Khoiria Fernanda; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Facility layout design is essential in supporting operational efficiency and smooth material flow within production systems. Specific Background: Ineffective layout arrangements often lead to excessive material handling distances and inefficient workflows in industrial environments. Knowledge Gap: Previous studies have not fully integrated relationship-based analysis and visual layout representation to systematically improve facility arrangement. Aims: This study aims to redesign facility layout by analyzing activity relationships and developing an improved layout configuration using Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD). Results: The analysis identified key relationships among workstations, which were translated into a structured layout design that reduces unnecessary movement and organizes workflow more effectively. The proposed layout demonstrates improved proximity between related activities and better spatial arrangement compared to the initial condition. Novelty: This study provides a structured application of ARC and ARD integration to connect relationship analysis with visual layout design in a specific industrial context. Implications: The findings offer practical guidance for improving facility layout planning to support more organized production flow and reduced material handling inefficiencies. Keywords: Facility Layout, ARC Method, ARD Method, Material Handling, Layout Redesign Key Findings Highlights Activity relationships guide spatial arrangement decisions Workflow organization reduces unnecessary movement Proposed configuration improves proximity among work units